Application of Copper Fungicide and Row Covers to Control Phytophthora Seedling Blight Disease on Cocoa - Febrilia Nur Aini; Teguh Iman Santoso; Sudarsianto Sudarsianto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Phytophthora seedling blight disease is one of the important diseases in cocoa. The disease is caused by the fungus of Phytophthora palmivora belongs to class Oomycetes. The aim of this research was to determine the effectiveness of the use of row covers and copper oxide fungicide applications to control seedling blight Phytophthora. Covering treatment was to place cocoa seedlings inside bamboo frame covered by transparent plastic in order to avoid from rainfall effect. The research was conducted in the Kaliwining Experimental Station at Indonesian Coffee and Cocoa Research Institute (ICCRI). Experiments were carried out four treatments and repeated 6 times. Each treatment consists of 100 seedlings planted in polybags and placed in the nursery area with a protective paranet. The treatment consisted of (1) row covers, (2) spraying of copper oxide 0.2%, (3) a combination of row covers and copper oxide 0.2% and (4) control (no covers and spray). Observations made 7 days after treatment with an interval of 7 days for 10 weeks. The results showed that row covers able to prolong the incubation period of the disease for 14 days, while the application of row covers + copper oxide 0.2% was able to save cocoa seedlings by 96.2%.